2018
DOI: 10.1111/eci.12934
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin measurement to screen medullary thyroid carcinoma: A prospective evaluation in a series of 2705 patients with thyroid nodules

Abstract: BackgroundTo prospectively evaluate the role of procalcitonin (PCT) in screening of patients with thyroid nodules for medullary thyroid carcinoma (MTC).Materials and methodsWe measured PCT in 2705 patients with thyroid nodules referred to our centre between January 2011 and December 2017. Those with a positive PCT were operated after positive confirmatory tests such as fine‐needle aspiration, measurement of calcitonin (CT) in serum and fine‐needle aspiration washouts or CT stimulation testing. Patients with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 36 publications
4
30
0
1
Order By: Relevance
“…It is recognised that measurement of this biomarker can allow earlier diagnosis than with imaging and fine needle aspiration (FNA). 4 In our case, not only was serum CT negative, but it was also shown to be negative on immunohistochemical staining of excised tissue. Immunohistochemistry is crucial in the diagnosis of CNMTC with particular attention given to markers shown in the investigations above.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…It is recognised that measurement of this biomarker can allow earlier diagnosis than with imaging and fine needle aspiration (FNA). 4 In our case, not only was serum CT negative, but it was also shown to be negative on immunohistochemical staining of excised tissue. Immunohistochemistry is crucial in the diagnosis of CNMTC with particular attention given to markers shown in the investigations above.…”
Section: Discussionsupporting
confidence: 50%
“…1 Pro-CT is the precursor of CT and has been shown to be a sensitive, reliable alternative to CT and is currently of most diagnostic use. 4 CGRP is secreted by MTC but also non-neoplastic C cells, and therefore may be of most use as an adjunct to diagnosis. 1…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Procalcitonin (PCT), the precursor of CT, circulates at low concentrations in healthy individuals; moreover, it has a concentration-independent and predictable in vivo half-life of 20-24 h and displays excellent in vitro stability in serum or plasma [11,12]. A strong correlation between PCT and CT levels was proven in patients with MCT and multiple studies confirmed equivalent high sensitivity of CT and PCT in detecting and monitoring MTC [13][14][15]. On balance, the above-mentioned studies suggested that PCT, being less affected by analytical, physiological, pharmacological and pathological factors that can influence results of serum CT values, could be a new standard of care in the management of MTC [16][17][18][19].…”
Section: Introductionmentioning
confidence: 95%
“…Thus, other MTC serum markers have been proposed, and ProCT has appeared as promising [ 6 ]. Interesting papers evaluated the role of ProCT in terms of prognosis and diagnosis of MTC with encouraging findings [ 30 31 ]. However, further studies are needed to reach evidence on its potential use for the initial assessment of MTC.…”
Section: Discussionmentioning
confidence: 99%